PPR com dupla trajetória de inserção: Relato de caso clínico - Uemura, Eduardo Shigueyuki [UNESP]; Silva, João Maurício Ferraz da [UNESP]; Kojima, Alberto Noriyuki [UNESP]; Torres, Carlos Rocha Gomes [UNESP]; Vieira, Cleiton Santos (Editora Cubo, 2017)
Removable Partial Dentures (RPD) with dual path of insertion are designed to overcome conventional RPD esthetic limitations, through the use of proximal undercuts for rigid direct retainers. Therefore, dual path RPD is considered a variation of conventional RPD. This paper reports a clinical case where proper function as well as excellent esthetics were obtained with this type of RPD.
Removable partial denture with dual path of insertion: Clinical case report
Keywords: Dual path design; Removable partial denture; Rotational path